Penerapan Manajemen Resiko pada Produk Pembiayaan di Lembaga Keuangan Mikro Syariah di KSPPS MUI Sekapuk Ujungpangkah Gresik - Muhammad Awaludin Islam; Sutopo Sutopo (Al-Muzdahir : Jurnal Ekonomi Syariah, 2022)
BMT KSPPS MUI is a sharia microfinance institution that manages these funds using financing products. financing products that are carried out are not free from risks, especially during the current pandemic. To prevent this risk from occurring, risk management is applied to financing products at the KSPPS MUI Sekapuk Branch. This research aims to: 1). know how to apply risk management to financing products and 2). find out what are the obstacles in implementing risk management in financing products. Because carrying out the implementation of risk management can prevent bad financing. The method used in collecting data in this study uses interviews, operations and documentation. While the research methodology uses a qualitative approach methodology. While the object is the BMT KSPPS MUI Sekapuk Branch. The results of this study show that 1). implementation of risk management using Surfe which is carried out according to the 5C standard, Billing rules that are applied to the maximum, NPF handling that uses rescheduling, returns and reconditioning, Use of reserve funds as an amticipation of losses from macat financing. 2). The ability to pay members has decreased, Members have moved domiciles, The macro economy has declined, The habit of members who often borrow in multiple places, Transferring or changing positions in internal financial institutions, Managers' ability to collect is not good.